Ortaöğretim 12. sınıf öğrencilerinin din kültürü ve ahlak bilgisi dersine yönelik değerlendirme ve beklentileri (Antalya örneği) - Sevim, Meryem (My University, 2024)
Bu araştırma, Antalya ilinde yer alan Fen Lisesi, Anadolu Lisesi ve Meslek Lisesi öğrencilerinden oluşan üç farklı grubun, Din Kültürü ve Ahlak Bilgisi (DKAB) ders müfredatına yönelik değerlendirmelerini ve beklentilerini incelemeyi amaçlamaktadır. Nitel araştırma yönteminin benimsendiği bu çalışmada, araştırmanın amaç ve kapsamı doğrultusunda 12. sınıf öğrencilerinden oluşan bir grupla derinlemesine mülakatlar gerçekleştirilmiştir. Mülakatlardan elde edilen veriler analiz edilmiş ve belirlenen temalar çerçevesinde yorumlanarak değerlendirilmiştir. Bu değerlendirme sürecinde ilgili literatüre atıflar yapılmıştır.

This research aims to examine the evaluations and expectations of three different groups of students from Science High Schools, Anatolian High Schools, and Vocational High Schools in Antalya regarding the Religious Culture and Moral Knowledge (RCMK) curriculum. Adopting a qualitative research methodology, in-depth interviews were conducted with a group of 12th-grade students in line with the study's objectives and scope. The data obtained from these interviews were analyzed and evaluated within the framework of the identified themes. Throughout this evaluation process, references were made to relevant literature.
Evaluation and expectations of 12th grade high school students regarding the religious culture and moral knowledge course : the case of Antalya
Keywords: Ahlak eğitimi; Antalya (Turkey); Antalya (Türkiye); Antalyal (Türkiye; Curriculum; Değerler; Din; Din Eğitimi; DKAB Dersi; Education; Eğitim; Islamic religious education; İslam dini eğitimi --- Antalya (Türkiye); Kazanım; Learning Outcomes; Moral education; Müfredat; Ortaöğretim; Öğrenim ve öğretim; Religion; Religious Culture and Moral Knowledge Course; Religious Education; Secondary Education; Socratic Method; Sokratik Metod; Study and teaching; Values